Leading with persuasion - Polansky, Barbara; Donaldson, Jack; Jackson, Dan; Video Visions (Los Angelas, CA : Video Visions, 1999)
Demonstrates the process of effective persuasion, showing the three essential steps of persuasion: preparation, presentation, and response. Useful in team building in any workplace setting
Title from title screen
Edited by Jack Donaldson ; music, Larry Wolff ; sound, Bob Eber
DVD format
Keywords: Persuasion (Psychology); Leadership